Nursing process and classifications schemes of nursing data - Stathopoulos, T; Merkouris, Anastasios (My University, 2002)
Rising health care costs and the need for enhancing the quality of health care are concerns of the hospitals throughout the world. Nursing documentation consumes excessive amounts of nursing time and influences directly the quality of clinical practice, research, administration and education. Recent developments in information technology have offered many alternatives to traditional systems of nursing process documentation. The main purpose of this article is to present the most widely accepted classification schemes, which can be used for the automation of the nursing process documentation in hospital settings, and discuss their implementation in our country.